Gender and financial inclusion: the critical role for holistic programming. Issue 8 (17th November 2019) - Arnold, Julia; Gammage, Sarah
ABSTRACT: This article introduces an edited collection on gender and financial inclusion that sets out to provide insights and evidence that enable practitioners to better reach women with digital financial services. The collection brings together four articles on financial inclusion that discuss a diverse range of interventions and experiences and explore the opportunities for and challenges to meaningful financial inclusion for women and non-literate and non-numerate populations. These articles interrogate the methods used to reach last mile communities and highlight the need for holistic, multi-layered programming that supports social norm change and addresses the particular constraints faced by members of these communities.